Characteristic properties of Planacon MCP-PMTs. (21st December 2021) - Melikyan, Y.A.; Slupecki, M.; Bearden, I.G.; Crowley, J.R.; Finogeev, D.A.; Garcia-Solis, E.J.; Guard, A.E.; Harton, A.V.; Kaplin, V.A.; Karavicheva, T.L.; Klay, J.L.; Morgan, I.; et al.
Abstract: A systematic investigation of Planacon MCP-PMTs was performed using 64 XP85002/ FIT-Q photosensors. These devices are equipped with microchannel plates of reduced resistance. Results of a study of their gain stability over time and saturation level in terms of the average anode current are presented. This information allows one to determine the lower limit of the MCP resistance for stable Planacon operation. The spread of the electron multiplication characteristics for the entire production batch is also presented, indicating the remarkably low voltage requirements of these MCP-PMTs. Detection efficiency and noise characteristics, such as dark count rate and afterpulsing level, are also reviewed.